Comparative Study of Chse Information System Voice Player Prototype in Tourist Destinations to Create Tourist Satisfaction - Supriadi, Bambang; Marcus, Ronal David; Bawono, Suryaning; Fauzie Said, Mochammad (Proceedings of International Conference of Graduate School on Sustainability, 2025)
Indonesian tourism still needs to improve in terms of developing quality tourism, namely, low destination management, suboptimal tourism services, and low human resource capacity. This study aims to determine whether to conduct a prototype trial and produce a CHSE health protocol sound player in the East Java tourism industry as an Information to create trust and satisfaction and increase tourist visits. Research Method: The CHSE Information System prototype trial was conducted at East Java tourist destinations as a prototype trial site to create tourist trust. This tool was tested on 398 tourists. The study results showed that satisfaction and trust values are interrelated. The CHSE Information System prototype trial results, conducted at East Java tourist destinations as a trial site, showed a difference between the two groups. The first group, namely tourist attractions that use CHSE loudspeakers, has higher Satisfaction and Trust values for tourists than the second group, namely those that do not use CHSE loudspeakers. This study clarifies the Spillover Theory and the Destination Social Responsibility Perspective. Making tourists behave positively, communally, and proactively so that environmentally conscious behavior occurs is important in handling traumatic events for tourists after COVID-19.